Mental capability of higher school students - Кorobeynikov G.V; Petrov G.S; Ulizko V.М (Kharkov National Pedagogical University, 2010)
Mental capability of higher school students of different specialties: technical (27 male and 35 female), natural (32 male and 30 female) and humanitarian (20 male and 26 female) were studied. The parameters: perception, attention, memory, thinking and mental capability was studied. The results are showed that the forming of psychophysiological organization of informational processing system in higher school students of different specialties is characterized by geterocronyisms with direction relation of specialty preparation. The learning of technical specialties to results of associative links determined and abstracts concepts forming under the analysis of the concretes objects. The natural specialties to promote of cognitive functions determined and times interval perception forming. The humanitarian specialties characterized of determined of attention and associative thinking functions.